1 \documentclass[12pt
]{article
}
6 T_
{pq
} = T_
{ij
} & = &
\frac{q_j
}{r^
3} \left[ 1 -
7 3\left(
\frac{r
}{r_c
}\right)^
{\!
2} +
8 2\left(
\frac{r
}{r_c
}\right)^
{\!
3}\right] (
\vec{p_i
}\times\vec{r
}) \\
9 T_
{qp
} = T_
{ji
} & = & -
\frac{q_i
}{r^
3} \left[ 1 -
10 3\left(
\frac{r
}{r_c
}\right)^
{\!
2} +
11 2\left(
\frac{r
}{r_c
}\right)^
{\!
3} \right] (
\vec{p_j
}\times\vec{r
}) \\
12 T_
{pp
} = T_
{ij
} & = & -
\frac{1}{r^
3}\left[1-
4\left(
\frac{r
}{r_c
}\right)^
{\!
3} +
13 e3
\left(
\frac{r
}{r_c
}\right)^
{\!
4}\right] (
\vec{p_i
} \times \vec{p_j
}) + \\
14 & &
\frac{3}{r^
5}\left[1-
4\left(
\frac{r
}{r_c
}\right)^
{\!
3} +
15 3\left(
\frac{r
}{r_c
}\right)^
{\!
4}\right] (
\vec{p_j
}\bullet\vec{r
})
16 (
\vec{p_i
} \times \vec{r
}) \\
17 T_
{pp
} = T_
{ji
} & = & -
\frac{1}{r^
3}\left[1-
4\left(
\frac{r
}{r_c
}\right)^
{\!
3} +
18 3\left(
\frac{r
}{r_c
}\right)^
{\!
4}\right](
\vec{p_j
} \times \vec{p_i
}) + \\
19 & &
\frac{3}{r^
5}\left[1-
4\left(
\frac{r
}{r_c
}\right)^
{\!
3} +
20 3\left(
\frac{r
}{r_c
}\right)^
{\!
4}\right] (
\vec{p_i
} \bullet \vec{r
})
21 (
\vec{p_j
} \times \vec{r
}) \\